DAKWAH ACTIVITIES AMONG MUSLIM MINORITY AND THE PREVENTION OF HATE SPEECH IN KUPANG, EAST NUSA TENGGARA - Kustini, Kustini; Eko Putro, Zainal Abidin (Analisa: Journal of Social Science and Religion, 2017)
During the last four months of the year 2016 in Jakarta in concomitant with the campaign period for 2017 governor election, the supposed hate speeches phenomenon sparkled everywhere either openly uttered or written expressed in social media as well as flyers spreading out in any places of the city. It seems that Muslim population of Jakarta was partly doing such hate speeches against incumbent Governor, a Chinese and a Christian, Basuki Tjahaja Purnama (Ahok), and his Muslim supporters. It is interesting to know how it happened in eastern Indonesia where Muslim is the minority. This qualitative research wants to elaborate and to explore to what extent the Islamic preaching deals with hate speech phenomenon in Kupang city. In order to reach data the researcher applied some methods such as in-depth interview, observation and literature study. In essence, Islamic proselytizing or dakwah in Kupang, East Nusa Tenggara, has been still persisted today. It targets solely for Muslim. Islamic proselytizing for non-Muslim is impossible because they are minority in this city. Technically, religious teaching doesn’t use loud speaker machine except for prayer callings (azan and iqamat)), Dakwah activist in Kupang usually tries to hinder the possibility of hate speech possibly sounded by Muslim clerics. In addition, there is a local mechanism run by mosque management for not being tolerance to hate speech through a set of guidance. Then, the issued guidance is sent to the invited preacher several days before to help preacher avoiding of hate speech.